Answers

2014-08-27T20:42:08+05:30
4×(-1)+(-1)-2×(-1)²+(-1)-1
= -4-1-2-1-1
= -9
1 2 1
2014-08-27T20:45:35+05:30
4x + x - 2x² + x - 1 
= 6x - 2x² - 1
x = - 1
6 * (- 1) -2 * (- 1)² - 1
- 6 - 2 * 1 - 1
- 9
The answer is - 9.
1 5 1
you can do one more thing, add up the same degree terms, before substituting x = -1, to -2(x^2) + 6x - 1,........... if u r seeing my comment, edit it, as u've solved it well, no warnings for this, but editing would be nice
yes u are right
Bro! Can you explain me in message?
now it looks nice ...
thanx buddy for your advise